Concurrent Infection With Multiple Human Papillomavirus Types Among Unvaccinated and Vaccinated 17-Year-Old Norwegian Girls. (17th November 2020) - Laake, Ida; Feiring, Berit; Jonassen, Christine Monceyron; Pettersson, John H O; Frengen, Torstein Gjølgali; Kirkeleite, Ingerid Ørjansen; Trogstad, Lill
Abstract: Background: Whether type-specific human papillomavirus (HPV) infection influences the risk of acquiring infections with other HPV types is unclear. We studied concurrent HPV infections in 17-year-old girls from 2 birth cohorts; the first vaccine-eligible cohort in Norway and a prevaccination cohort. Methods: Urine samples were collected and tested for 37 HPV genotypes. This study was restricted to unvaccinated girls from the prevaccination cohort (n = 5245) and vaccinated girls from the vaccine-eligible cohort (n = 4904). Risk of HPV infection was modelled using mixed-effect logistic regression. Expected frequencies of concurrent infection with each pairwise combination of the vaccine types and high-risk types (6/11/16/18/31/33/35/39/45/51/52/56/58/59) were compared to observed frequencies. Results: Infection with multiple HPV types was more common among unvaccinated girls than vaccinated girls (9.2% vs 3.7%). HPV33 and HPV51 was the only HPV pair that was detected together more often than expected among both unvaccinated ( P = .002) and vaccinated girls ( P < .001). No HPV pairs were observed significantly less often than expected. Conclusions: HPV33 and HPV51 tended to be involved in coinfection among both unvaccinated and vaccinated girls. The introduction of HPV vaccination does not seem to have had an effect on the tendency of specific HPV types to cluster together. Abstract : Concurrent HPV infections and associations between HPV types were investigated among 17-year-old Norwegian girls from the first vaccine-eligible cohort and a prevaccination birth cohort. Introduction of HPV vaccine did not seem to influence clustering of HPV types.